Estimation and validation of standalone SCATSAT-1 derived snow cover area using different MODIS products. Issue 27 (13th December 2022) - Singh, Sartajvir; Tiwari, Reet Kamal; Sood, Vishakha; Kaur, Ravneet; Singh, Simrandeep; Prashar, Shivendu
Abstract: In the present work, the scatterometer satellite (SCATSAT-1) has been implemented and validated to provide the near-real-time estimation of snow cover area (SCA) in the Western Himalayas, India. The SCA derived from standalone SCATSAT-1 L4 (Level-4 India) products, i.e. sigma-nought ( σ ° ), and gamma-nought ( γ ° ) has been validated with different MODIS products individually, i.e. MOD02 L1B (calibrated-radiances) derived NDSI (normalized difference snow index), MOD10A1 L3 (daily composite snow cover), and MOD10A2 L3 (8-Day composite snow cover). The experimental outcomes confirm the potential of SCATSAT-1 in estimating the SCA with respect to other MODIS products and also, suggested the utilization of the different MODIS products for referencing/validation in different scenarios. The findings of this paper suggest that SCATSAT-1 offers the near real-time mapping and monitoring of large-scale snow extent at the global level even under cloudy conditions.